TERAPI CERMIN TERHADAP KEKUATAN OTOT EKSTREMITAS PADA PASIEN STROKE - Luluk Cahyanti (Lembaga Pengembangan Kinerja Dosen, 2022)
Stroke is a disease or functional disorder of the brain in the form of nerve paralysis due to obstruction of blood flow to the brain. Decreased blood flow to the brain can be caused by blocked blood vessels in the brain. It can also be caused by the rupture of blood vessels to the brain. In simple terms, acute stroke is defined as a brain disease due to cessation of blood supply to the brain due to bleeding (hemorrhagic stroke) or blockage (non-hemorrhagic stroke). According to the WSO (World Stroke Organization) in 2016 more than 67.5 million people in the world experienced an ischemic stroke and 15 million people in the world experienced a hemorrhagic stroke. Nationally, the prevalence of stroke in Indonesia according to the Ministry of Health of the Republic of Indonesia in 2018 is estimated at 2,120,362 people who suffer from stroke. Brain damage from a stroke can cause various symptoms such as paralysis or weakness in one half of the body that occurs suddenly, where the most characteristic symptom is hemiparesis (reduced muscle strength of one limb). Muscle strength is the ability of muscles to produce tension and power during maximum effort both dynamically and statically or in other words muscle strength is the maximum ability of muscles to contract. Non-pharmacological therapy that can be done to increase extremity muscle strength in stroke patients is mirror therapy. Mirror therapy is a form of rehabilitation that relies on motor imagery, where the mirror will provide visual stimulation that tends to be imitated like a mirror on body parts that are disturbed by healthy body parts. The purpose of this case study is to describe the application of mirror therapy to extremity muscle strength in stroke patients. The writing method uses a descriptive method with a nursing care process approach, the samples taken are 2 respondents.